Organizational Justice, Professional Identification, Empathy, and Meaningful Work During COVID-19 Pandemic: Are They Burnout Protectors in Physicians and Nurses? - Correia, Isabel; Almeida, Andreia E. (Frontiers in Psychology, 2020)
Burnout has been recognized as a serious health problem. In Portugal, before Covid-19 Pandemic, there were strong indicators of high prevalence of burnout in physicians and nurses. However, the Portuguese Health Care Service was able to efficiently respond to the increased demands. This study intends to understand how psychosocial variables might have been protective factors for burnout in physicians and nurses in Portugal. Specifically, we considered several psychosocial variables that have been found to be protective factors for burnout in previous research and we compared their predictive and unique impact in the prediction of burnout. These variables are perceptions of justice (distributive, procedural, justice from colleagues, justice from patients and their families), professional identification, meaningful work and empathy. We also included workload , as a risk factor, and controlled other variables that can be confounds for burnout, such as socio-demographic variables), ideological variables (religiosity, political orientation), and specific variables related with Covid-19 pandemic. The sample of the present study is composed by 229 physicians (aged between 23 and 70 years, M = 36.54; SD = 10.72; 48% male and 52% female) and 268 nurses (aged between 22 and 69 years, M = 34.96; SD = 9.52; 27% male and 73% female). An online survey was created using Qualtrics and participants were recruited via Facebook and LinkedIn. The data were collected during 29 days (between the 45th and the 74th days after the first diagnosed case of Covid-19 in Portugal). The results showed that procedural justice was a significant protector for both dimensions of burnout both in physicians and nurses. Professional identification remained a significant protective factor for disengagement (both in physicians and nurses) and for exhaustion in physicians, but not for exhaustion in nurses. Workload was a significant risk factor, except for disengagement in physicians. This study suggests several focus that might be simultaneously and independently addressed in interventions for reducing the risk of burnout or preventing it from occurring in the first place, by decreasing workload and promoting procedural justice and professional identification.